Systematics and phylogeny of the adean genera Leptopeltus Bernhauer and Leptopeltoides gen. nov. (Coleoptera: Staphylinidae), with biogeographical notes - Chani Posse, Mariana Raquel (2013)
The genus Leptopeltus Bernhauer, 1906 (Staphylininae: Staphylinini), distributed from western Venezuela to northwestern Argentina, is revised using characters of external morphology and male and female genitalia. Leptopeltus comprises five species, of which two are described as new: L. carchiensis and L. weyrauchi. Other valid species of the genus are: Leptopeltus flavipennis (Erichson), L. montivagans Bernhauer and L. netolitzkyi Bernhauer. Lectotypes are designated for Leptopeltus flavipennis (Erichson) and L. netolitzkyi Bernhauer. Leptopeltoides gen. nov., from western Colombia and Ecuador, is described for the following four new species: Le. chingazensis, Le. columbiensis, Le. ecuatoriensis and Le. napoensis. Both genera are revised herein, with keys for identification, diagnoses, descriptions, illustrations, a cladogram, and distributional maps. The cladistic analysis shows that Leptopeltus and Leptopeltoides are both monophyletic genera and sister groups and they belong to a natural group of Neotropical genera of Philonthina (Staphylinini).